Positioning of Pharmacies and Reverse Logistics in the Control of Obsolete Drugs - Silva, André Luiz Emmel; Moraes, Jorge André Ribas; Rehbein, Adriel; Bencke, Daniel; Gerhard, Guilherme (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The theme Reverse Logistics has been discussed and encouraged in the business with greater emphasis due to the growth of environmental awareness. It deals with the importance of recycling, recycle and reuse in order to make companies agents and greater awareness of their importance as agents of change in attitudes to society as a whole raising their care about the preservation of the environment and being well understood by stakeholders as a competitive, placing them in different positions against competitors. Through a literature search on disposal of medicines into disuse, along with a case study in pharmacy, it was possible to analyze the current situation on compliance and awareness regarding existing regulations related to the subject. The methodology used was based on structured interviews, emphasizing issues related to the conduct of disposal, level of guidance and adherence to regulatory standards. 50 pharmacies were interviewed, verifying that despite all are implementing a program allocation, few understand about the destination or know what happens to the waste.